Breath healing therapy for the treatment of psychiatric and stress-related medical conditions - Venera Telzhan (Progress in Science, 2023)
This article discusses the use of breath healing therapy as an additional therapy for psychiatric and stress-related medical conditions. Breath healing therapy involves techniques such as diaphragmatic breathing and alternate nostril breathing, which aim to optimize breathing patterns and promote relaxation and self-awareness. Research has demonstrated that breathing exercises can influence physiological and psychological responses to stressors, and recent studies have provided evidence for the effectiveness of breathing healing therapy in the treatment of various psycho emotional issues. Thе purpose of the research is to conduct a systematic literature review to evaluate the efficacy of several main breathing techniques for managing stress-related disorders and preventing psychiatric diseases. The article highlights the potential of breath healing therapy as a non-pharmacological treatment option for individuals with these conditions, and suggests the need for further research to better understand its underlying mechanisms and to evaluate its effectiveness and safety in different populations.